PENGARUH STRES KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN KAMPAR - Rahmat Taufiq; Yulizar Baharuddin (STIE Bangkinang Publishing, 2020)
This study aims to determine the effect of work stress and motivation on employee performance in the Kampar District Regional Disaster Management Agency. Job stress is a feeling experienced by employees in dealing with work. This work stress, among others, unstable emotions, feelings of displeasure, can not relax, anxiety, tension, nervousness, increased blood pressure, and experiencing indigestion. Motivation is the encouragement of the individual to carry out certain activities in order to meet their needs so that the goal is finally achieved. While the performance is the level of success achieved by an employee in his work, which looks inside how the quality and quantity of an employee in doing a job. The analysis in this study uses multiple analysis with 65 respondents. Sampling uses the census method, while the hypothesis testing in this study uses the f test and t test. Based on the results of the study it can be concluded that simultaneously and partially, work stress and motivation significantly influence performance.